Photochemical Water Splitting by Bismuth Chalcogenide Topological Insulators - Rajamathi, Catherine R.; Gupta, Uttam; Pal, Koushik; Kumar, Nitesh; Yang, Hao; Sun, Yan; Shekhar, Chandra; Yan, Binghai; Parkin, Stuart; Waghmare, Umesh V.; Felser, Claudia; Rao, C. N. R. (ChemPhysChem, 2017)
As one of the major areas of interest in catalysis revolves around 2D materials based on molybdenum sulfide, we have examined the catalytic properties of bismuth selenides and tellurides, which are among the first chalcogenides to be proven as topological insulators (TIs). We find significant photochemical H2 evolution activity with these TIs as catalysts. H2 evolution increases drastically in nanosheets of Bi2Te3 compared to single crystals. First-principles calculations show that due to the topology, surface states participate and promote the hydrogen evolution.
CRIS-Team Scopus Importer:2022-04-14
Keywords: bismuth; first-principles calculations; hydrogen evolution; photochemical water splitting; topological insulators